Executive Coaching: A Guide for the HR Professional - Anna Marie Valerio, Robert J. Lee (John Wiley & Sons, Inc. Reproduced, 2005)
he goal of this book is to provide a concise but lucid explanation and deriva-tion of the fundamentals of spread-spectrum communication systems. Although spread-spectrum communication is a staple topic in textbooks on digital com-munication, itstreatment is usually cursory, and the subject warrants a moreintensive exposition. Originally adopted in military networks as a means of ensuring secure communication when confronted with the threats of jammingand interception, spread-spectrum systems are now the core of commercial ap- plications such as mobile cellular and satellite communication. The level of presentation in this book is suitable for graduate students with a prior graduate-level course in digital communication and for practicing engineers with a solid background in the theory of digital communication. As the title indicates, this book stresses principles rather than specific current or planned systems, whichare described in many other books. Although the expositionemphasizes the-oretical principles, the choice of specific topics is tempered by my judgment of their practical significance and interest to both researchers and systemdesign-ers. Throughout the book, learning is facilitated by many new or streamlined derivations of the classical theory. Problems at the end of each chapter areintended to assist readers in consolidating their knowledge and to provide prac-tice in analytical techniques. The book is largelyself-containedmathematically because of the four appendices, which give detailedderivations of mathematicalresultsused in the main text.In writing this book, I have relied heavily on notes and documents prepared and the perspectives gained during my work at the US Army Research Labo-ratory. Many colleagues contributed indirectly to this effort. I am grateful tomy wife, Nancy, who provided me not only with her usual unwavering support but also with extensive editorial assistance.